1999
DOI: 10.1038/sj.bjc.6690365
|View full text |Cite
|
Sign up to set email alerts
|

Camptothecin sensitizes androgen-independent prostate cancer cells to anti-Fas-induced apoptosis

Abstract: Despite expressing both Fas and Fas ligand, DU145 and LNCaP prostate cancer cells were resistant to anti-Fas-induced cell death. Resistance to Fas-mediated cytotoxicity could be overcome in DU145, but not in LNCaP, cells by pretreating cells with sublethal doses of cytotoxic drugs, such as camptothecin. Activated caspases were shown to be required for this cytotoxicity. Indeed, poly(ADP-Ribose) polymerase was shown to be proteolytically cleaved in cells treated with camptothecin plus anti-Fas, but not in cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
2
31
1
Order By: Relevance
“…DU145 cells express both Fas and FasL, but are resistant to anti-Fas-mediated apoptosis, unless pretreated with sublethal doses of a cytotoxic drug, such as camptothecin (Costa-Pereira and Cotter, 1999). Here, we show that treatment of DU145 prostate cancer cells with anti-Fas failed to activate SAPK/JNK.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…DU145 cells express both Fas and FasL, but are resistant to anti-Fas-mediated apoptosis, unless pretreated with sublethal doses of a cytotoxic drug, such as camptothecin (Costa-Pereira and Cotter, 1999). Here, we show that treatment of DU145 prostate cancer cells with anti-Fas failed to activate SAPK/JNK.…”
Section: Discussionmentioning
confidence: 74%
“…We have previously shown that activated caspases were required for this cytotoxicity (Costa-Pereira and Cotter, 1999). However, inhibition of caspase activity by the pan-inhibitor z-VAD had no effect on SAPK/JNK activation following concomitant treatment of cells with camptothecin and anti-Fas, suggesting that SAPK/JNK activation was not caspase-dependent.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…193 In addition, we have recently shown that a combinatory treatment of androgen-independent DU145 cells with sublethal concentrations of camptothecin and very low concentrations of anti-Fas IgM, will kill 75 ± 95% of a cell culture population in 24 h. 194 Fas (CD95aAPO-1) belongs to the nerve growth factoratumour necrosis factor (NGFaTNF) receptor family, and its main function is the induction of apoptosis in a variety of cell types. 195,196 The prostatic epithelium is one of the few tissues to co-express Fas and FasL, along with other immune privileged tissues which are marked by apoptotic turnover, and there is evidence for an in vivo role for Fas signalling in the hormonal regulation of the normal, differentiated prostatic epithelium.…”
Section: Medical Approaches In the Management Of Prostate Cancermentioning
confidence: 99%